A CLINICAL STUDY ON EFFICACY OF JEEVANTYAADI GHRITA IN SUSHKAKSHIPAAKA (DRY EYE) - Dastapure, Mamata; Shekar, Veena; K, Sujathamma; KV, Mamatha; Mishra, Baidyanath (International Journal of Ayurveda and Pharma Research, 2015)
Dry eye also known as keratoconjuctivitis sicca or xerophthalmia, is a multi-factorial disease that results in discomfort, visual disturbance and tear film instability with potential damage to the ocular surface on progress of the disease, if proper steps are not adopted for prevention or management from the beginning of the disease. Dry eye is accompanied by increased osmolarity of the tear film and inflammation of the ocular surface. It is a commonest ocular disorder especially among the elderly because of reduction in tear film secretion. As far as the prevailing practices available for dry eye are concerned, no specific treatment is effective addressing the symptoms visualized in dry eye. The condition dry eye can be well compared to Sushkakshipaaka (Sushka=Dry, Akshi=Eye, Paaka=inflammation) explained in Ayurveda owing to its simulating clinical features and pathogenesis. Various regulated principles of management are in place addressing the above clinical complications by reaching the target tissues and receptors for enriching the ocular surface, and thus extending milestone in recovering from dry eye symptoms. Thus patients (n=10) registered with dry eye in outpatients department of Shalakya tantra of Shri Kalabyraveshwara Ayurveda Medical College Hospital and Research Centre Bangalore, were taken up for the study and treated with Jeevantyadi ghrita tarpana five days of two sittings with an interval of ten days. There was no drops outs and treatment event was successful.